Comparative Insights into Vital Pulp Therapy Techniques - Nirav Vyas; Diksha Sharma (National Board of Examinations Journal of Medical Sciences, 2025)
Vital pulp therapy encompasses a spectrum of biologically based procedures aimed at preserving the vitality of dental pulp following exposure due to caries, trauma, or mechanical factors. This narrative review provides a comprehensive overview of six core VPT techniques—indirect pulp capping, direct pulp capping, miniature pulpotomy, partial pulpotomy, full pulpotomy, and deep pulpotomy—with an emphasis on their historical development, clinical protocols, and reported success rates. Indirect and direct pulp capping remain foundational techniques, particularly in minimally or non-exposed pulps, with recent studies supporting high clinical success when appropriate sealing and case selection are observed. Miniature pulpotomy has emerged as a promising modification of direct capping, offering favourable outcomes through minimal pulp removal and improved material-pulp interaction. Partial and full pulpotomies continue to gain clinical relevance in managing both immature and mature permanent teeth, with comparable outcomes to root canal therapy in selected cases of irreversible pulpitis. Deep pulpotomy, though conceptually aligned with full pulpotomy, remains an underexplored technique with limited evidence supporting its use. Despite favourable clinical performance across various VPT modalities, inconsistencies in case selection, terminology, and treatment protocols highlight the need for standardized guidelines and further long-term investigations. This review underscores the evolving scope of VPT as a conservative and biologically driven alternative to conventional endodontic therapy.